Peran Ombudsman Republik Indonesia sebagai Lembaga Pengawas Pelayanan Publik - Resty Lestari (CV Rewang Rencang, 2025)
The implementation of good public services will encourage the realization of Good Governance. The Ombudsman as one of the supervisory institutions is expected to create an effective and efficient public service implementation. This study examines the legal regulations and their implementation related to the role of the Ombudsman of the Republic of Indonesia as a public service supervisory institution. The approach in this study uses a legislative and conceptual approach with a normative juridical research type, the results of the study indicate that the Ombudsman of the Republic of Indonesia as a public service supervisory institution only provides recommendations so that many still do not implement these recommendations. The conclusion of this study is the still weak implementation of sanctions against the reported party/superior of the reported party who does not implement the recommendations is only subject to administrative sanctions as regulated in Article 39 of Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia.